The effect of customer experience, customer satisfaction and word of mouth intention on customer loyalty: The moderating role of consumer demographics - Wilbert Manyanga; Charles Makanyeza; Zororo Muranda (Cogent Business & Management, 2022)
Customer experience, satisfaction and word-of-mouth intention contribute a crucial part in enhancing customer loyalty in the banking sector. This study examines the moderators of the effect of customer experience, satisfaction and word-of-mouth intentions on customer loyalty. Data were collected from bank customers (n~=~650) using a structured questionnaire through a cross-sectional survey in Harare, Zimbabwe. Customer experience, satisfaction and word-of-mouth intention were found to have a direct positive effect on loyalty. Age was found to moderate the effect of customer satisfaction on loyalty. However, gender, education and income did not moderate the effect of customer satisfaction on loyalty. These results contribute to the existing body of services marketing literature. Banks are advised to consider customer experience, satisfaction, word-of-mouth intention and age when designing strategies to improve customer loyalty.
Keywords: 650; customer loyalty; customer satisfaction; banking; customer experience; word of mouth intention